IMPLEMENTASI CSR PT ASIA FORESTAMA RAYA TERHADAP PEMBERDAYAAN PEREKONOMIAN MASYARAKAT PADA MASA PANDEMI COVID-19 - Hasnati Hasnati; Sandra Dewi; Andrew Shandy Utama (Ensiklopedia Social Review, 2021)
PT Asia Forestama Raya is a forest product processing factory for the wood industry's raw materials. Based on Article 74 Paragraph (1) of Law Number 40 of 2007 concerning Limited Liability Companies, it is stipulated that companies that carry out their business activities in the natural resources sector and / or fields related to natural resources are required to implement CSR. In Article 10 of Riau Provincial Regulation Number 6 of 2012 concerning Corporate Social Responsibility in Riau Province, it is stated that CSR programs can take the form of community economic empowerment. This research aims to explain the implementation of PT Asia Forestama Raya's CSR on community economic empowerment during the Covid-19 pandemic. The method used in this research is socio-legal research. During the Covid-19 pandemic, the public really expected a real contribution from PT Asia Forestama Raya. PT Asia Forestama Raya's obstacle in implementing community economic empowerment in Limbungan Village is that the financial condition of PT Asia Forestama Raya is currently in an unstable state. Efforts that can be made by the people of Limbungan Village if PT Asia Forestama Raya doesn’t carry out a CSR program are to convey their aspirations to Commission IV of DPRD Pekanbaru City. Based on Article 32 of Riau Provincial Regulation Number 6 of 2012 concerning Corporate Social Responsibility in Riau Province, it is stated that if PT Asia Forestama Raya doesn’t carry out CSR towards empowering the community's economy, the company can be subject to administrative sanctions by the Pekanbaru City Government.